ANALYSIS OF RESIDUAL CHLORINE CONCENTRATION IN DISTRIBUTION NETWORK OF DRINKING WATER SUPPLY AT ISTANA DIENG II RESIDENCE OF MALANG, EAST JAVA, INDONESIA - Moh. Zainal Bahrudin; Anie Yulistyorini; Titi Rahayuningsih (INDONESIAN JOURNAL OF URBAN AND ENVIRONMENTAL TECHNOLOGY, 2022)
The drinking water distribution network in Istana Dieng residence is categorized as an isolated network because it does not connect with the other water distribution networks provided by the Malang Water Company (Perusahaan Daerah Air Minum, PDAM). For this reason, the residual chlorine of the isolated distribution network needs to be monitored regularly. Aim: This study aims to observe residual chlorine distribution patterns and investigate the effect of distribution distance, pH, and temperature on residual chlorine concentration in the water distribution network. Methodology and Results: Analytical survey method with a cross-sectional approach was used in this study. The field survey results and the water analysis were inputted into the ArcGIS 10.6 software to generate an Isoconcentration map. Correlation and regression analysis were conducted using SPSS 16.0. Conclusion, significance and impact of study: The results showed that 65% of the residual chlorine concentration in the drinking water distribution network Istana Dieng residence did not meet the quality standard (<0.2 mg/l). Twenty-six sample points showed a value of 0.1 mg/l, which was caused by the pipe's physical condition and the use of wells connected to the PDAM network. There was a significant correlation between distance and residual chlorine concentration. The significant correlation between pH and residual chlorine concentration showed a value of -0.690. The correlation between temperature and residual chlorine concentration was -0.633. It was proven that the lower the residual chlorine concentration, the higher the pH and temperature values in the distribution network.